The entrepreneur's information sourcebook : charting the path to small business success - Awe, Susan C., 1948- (Santa Barbara, Calif. : Libraries Unlimited, 2012)
"This book provides the expert guidance and up-to-date print and web resources an entrepreneur may need to make his business thrive and grow, from inception and information gathering, to raising capital, to marketing methods and human resource concerns. Nearly half of the resources in this updated edition are new, and the essays have also been updated to reflect current business practices. This book is an essential tool that provides quick and easy access to the information every small business owner needs."--Back cover.
Introduction -- Are you an entrepreneur? -- Research, statistics, and information gathering -- Start up -- Your business plan -- Ups and downs of franchising -- Raising capital -- Marketing and advertising -- The internet and selling globally -- Management -- Personnel/human resources -- Legal/taxes -- Working with the government -- Competitive analysis -- Growing your business and moving on -- Glossary -- Index.
Includes index.
Keywords: New business enterprises; Entrepreneurship